Complex components of Shengmai formula interact with organic cation transporter 2 (OCT2) in MDCK cells. (23rd May 2023) - Meng, Chao; Zhong, Lanping; Lu, Ting; Gu, Qi; Du, Xinyue; Liu, Fanglan; Xia, Chunhua
Abstract: Ethnopharmacological relevance: Shengmai formula (SMF) is a well-known Chinese herbal compound preparation, which is utilized extensively for the treatment of myocardial ischemia, arrhythmia and other life-threatening conditions. Our previous researches have shown that some of the active ingredients in SMF can interact with organic anion transport polypeptide 1B1 (OATP1B1), breast cancer resistance protein (BCRP) and organic anion transporter 1 (OAT1), etc. Organic cation transporter 2 (OCT2) is a highly expressed uptake transporter in the kidney, and its interaction with the major active components in SMF remains unclear. Aim of the study: We purposed to explore OCT2-mediated interactions and compatibility mechanisms of the main active compounds in SMF. Materials and methods: Fifteen active ingredients of SMF, including ginsenoside Rb1, Rd, Re, Rg1, Rf, Ro and Rc, methylophiopogonanone A and B, ophiopogonin D and Dˊ, schizandrin A and B, schizandrol A and B, were selected to investigate OCT2-mediated interactions in Madin-Darby cacine kidney (MDCK) cells stably expressing OCT2. Results: Among the above 15 main active components, only ginsenosides Rd, Re and schizandrin B could significantly inhibit the uptake of 4-(4-(dimethylamino)styryl)-N-methyl pyridiniumiodide (ASP + ), a classical substrate of OCT2. Ginsenoside Rb1 and methylophiopogonanone A can be transported by MDCK-OCT2 cells, and their uptake was significantly reduced when OCT2 inhibitor decynium-22 was added. Ginsenoside Rd could remarkably reduce the uptake of methylophiopogonanone A and ginsenoside Rb1 by OCT2, ginsenoside Re only decreased the uptake of ginsenoside Rb1, while schizandrin B had no effect on the uptake of both. Conclusions: OCT2 mediates the interaction of the major active components in SMF. Ginsenosides Rd, Re and schizandrin B are the potential inhibitors of OCT2, while ginsenosides Rb1 and methylophiopogonanone A are the potential substrates of OCT2. There is an OCT2-mediated compatibility mechanism among these active ingredients of SMF. Graphical abstract: Image 1 Highlights: Ginsenosides Rd, Re and schizandrin B are potential inhibitors of organic cation transporter 2 (OCT2). Ginsenosides Rb1 and methylophiopogonanone A are potential substrates of OCT2. OCT2 mediates the interaction of major active components in Shengmai Formula (SMF). There is an OCT2-mediated compatibility mechanism between these active ingredients of SMF.